Genetic Factor in Etiology of Febrile Seizures - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Istanbul, Turkey, studied R43Q mutations of the gamma-aminobutyric acid A receptor (GABRG2) gene, located on the long arm of chromosome 5, in 44 children with febrile seizure (FS) and 49 without.